2003
DOI: 10.1523/jneurosci.23-07-02789.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cats on the Treadmill: Changes in Load Pathways

Abstract: Treadmill training and clonidine, an ␣-2 noradrenergic agonist, have been shown to improve locomotion after spinal cord injury. We speculate that transmission in load pathways, which are involved in body support during stance, is specifically modified by training. This was evaluated by comparing two groups of spinal cats; one group (n ϭ 11) was trained to walk until full-weight-bearing (3-4 weeks), and the other (shams; n ϭ 7) was not. During an acute experiment, changes in group I pathways, monosynaptic excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Moreover, modified properties of motoneurons could not explain increased monosynaptic reflexes in chronic spinal animals Hochman and McCrea, 1994). In this study, training did not modify AHP duration, which varies with input resistance and membrane time constant (Gustafsson and Pinter, 1984;Côté et al, 2003). Moreover, a general change in membrane responsiveness is unlikely to explain the simultaneous increase in R1 amplitude and decrease in R3 amplitude observed in the same motoneuron (Table 2).…”
Section: Plasticity In Spinal Pathwaysmentioning
confidence: 56%
See 3 more Smart Citations
“…Moreover, modified properties of motoneurons could not explain increased monosynaptic reflexes in chronic spinal animals Hochman and McCrea, 1994). In this study, training did not modify AHP duration, which varies with input resistance and membrane time constant (Gustafsson and Pinter, 1984;Côté et al, 2003). Moreover, a general change in membrane responsiveness is unlikely to explain the simultaneous increase in R1 amplitude and decrease in R3 amplitude observed in the same motoneuron (Table 2).…”
Section: Plasticity In Spinal Pathwaysmentioning
confidence: 56%
“…In both humans and cats recovering from SCI, progressively increasing weight bearing improves stepping ability Edgerton et al, 1992;Harkema et al, 1997). Moreover, we recently showed that step training modified transmission from group I afferents of extensors in spinal cats (Côté et al, 2003). However, cutaneous afferents are also activated by locomotor movements and may participate in recovery.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…As seen in previous sections of this review (e.g., the section by Schwab), such neuroplasticity may occur via regeneration of damaged fibers or sprouting of undamaged fibers (Raineteau and Schwab, 2001;Fouad et al, 2001;Raineteau et al, 2002;Bareyre et al, 2004;Ballermann and Fouad, 2006). Neuroplastic changes can also be manifest in the spinal cord itself below the lesion (Grillner, 1981;Rossignol, 1996Rossignol, , 2006Côté et al, 2003;Côté and Gossard, 2004;Frigon and Rossignol, 2006;Rossignol et al, 2006).…”
Section: A Synergy Between T-cell-based Vaccination and Adult Neural mentioning
confidence: 83%